Gravity investigation of the Bukit Bunuh impact crater at Lenggong,Perak, Malaysia - Abdul Rahim Samsudin,; Abdul Rahim Harun,; Mohd. Hariri Arifin,; Umar Hamzah,; Mokhtar Saidin,; M Shyeh Sahibul Karamah, (Universiti Kebangsaan Malaysia, 2012)
An archeological study, conducted by the Archaeological Global Research Centre, Universiti Sains Malaysia shows the evidence of shock metamorphisms (suevite breccia) and crater morphology at Bukit Bunuh in Lenggong area of north Perak, Malaysia. A regional gravity survey focusing at Bukit Bunuh and its surrounding area was conducted to justify the occurrence and to determine the diameter and subsurface geological structure of the Bukit Bunuh impact crater. The gravity survey, using a Scintrex CG5 gravity meter, comprises 476 gravity stations with a 500 m spacing covering an area of approximately 160 km2. The elevation of the gravity stations were obtained by using a pair of Wellace and Tiernan altimeters. The gravity data were corrected for drift, free air, bouguer, latitude and terrain in order to produce a corrected gravity data of the study area. The data were processed and analysed using Oasis Montaj (Geosoft software) to produce bouguer, residual, Total Horizontal Derivative (THD) residual, regional and Total Horizontal Derivative (THD) regional anomaly maps for qualitative and quantitative interpretations. The bouguer gravity map shows relatively low negative anomaly with nearly circular shaped contour around the Bukit Bunuh area. This anomaly was interpreted as the remnant of meteorite impact structure with rounded shaped crater in the study area. The bouguer anomaly map showed that the Bukit Bunuh impact crater has a diameter of approximately 2.5 km. The impact structure was successfully modeled as a complex impact crater with maximum depth of about 300 m. The bouguer anomaly map also shows the possible occurences of at least two more impact craters located in the northeast and southeast areas of the Bukit Bunuh crater and these structures need further investigation for confirmation.